The Qur’an and Muslim men’s marriages to women of the people of the book (Ahl Kitab) (an interpretive essay of Ahl Kitab on Qur’an 5:5) - Zubair; Muhammad Faisal Hamdani (Cogent Arts & Humanities)
The phenomenon of interfaith marriage is currently still a long debate related to the legal status of religion and the state. This debate starts with Islamic law, which legalises marriage with ahl alkitab women. Meanwhile, the consensus of the ‘ulamā’ who are members of MUI (the Indonesian Council of Ulama)) and Islamic organisations prohibits this type of marriage. This contrasting difference makes the state law in the Marriage Law also unclear in regulating this type of marriage, resulting in a legal vacuum and causing a prolonged polemic. This article examines the interfaith marriage debate in the interpretation’s context of Qur’an 5:5 which is clashed with legal products resulting from the consensus of the ‘ulamā’ and state law. This study uses a qualitative approach with the method of document analysis. This study argues that although the status of interfaith marriages was clear in the early days of Islam, this is not the case in the contemporary era. The author thinks that implementing this legal status of marriage in Indonesia needs to be returned to the original law when Qur’an 5:5 was revealed. Regarding concerns about threats that become the ‘illat (cause) of the prohibition of marriage, this does not apply absolutely.